2010
DOI: 10.2147/opth.s10162
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial conjunctivitis

Abstract: Clinical questionWhat is the best treatment for bacterial conjunctivitis?ResultsTopical antibiotics expedite recovery from bacterial conjunctivitis. The choice of antibiotic usually does not affect outcome.ImplementationRecognition of key distinguishing features of bacterial conjunctivitis Pitfalls that can be recognized in the history and physical examinationChoice of antibioticWhen to refer for specialist treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 2 publications
0
12
0
Order By: Relevance
“…Their search sources were from ovid MEDLINE, PubMed, Cochrane Library, NHS evidence and Clinical Evidence. They concluded that bacterial conjunctivitis is caused by Staphyloccus species in adults and by Streptococcus pneumoniae and the Gramnegative organisms Haemophilus influenxae and Moraxella catarrhalis in children (Hutnik et al, 2010). However, Haas et al (2012)from the USA reported that the most prevalent species in their study was H. influenzae, followed by Staphylococcus epidermidis, Staphylococcus aureus, the Streptococcus mitis group, and Streptococcus pneumoniae.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Their search sources were from ovid MEDLINE, PubMed, Cochrane Library, NHS evidence and Clinical Evidence. They concluded that bacterial conjunctivitis is caused by Staphyloccus species in adults and by Streptococcus pneumoniae and the Gramnegative organisms Haemophilus influenxae and Moraxella catarrhalis in children (Hutnik et al, 2010). However, Haas et al (2012)from the USA reported that the most prevalent species in their study was H. influenzae, followed by Staphylococcus epidermidis, Staphylococcus aureus, the Streptococcus mitis group, and Streptococcus pneumoniae.…”
Section: Discussionmentioning
confidence: 97%
“…Although most cases of conjunctivitis are self limited, treatment with antibiotics has been shown to decrease the discomfort and duration of the symptoms. Antibiotic treatment also reduces contagious spread (Hutnik, Mohammad & Shahi, 2010;Lietman et al, 1984;Morrow & Abbott, 1998;Tarabishy & Jeng, 2008).Incidence of bacterial conjunctivitis, common pathogens causing it and their susceptibility to existing antibiotics differ from country to country (Adebayo et al, 2011;Azari & Barney, 2013;Haas, Gearinger, Hesje, Sanfilippo, & Morris, 2012;Pichichero, 2011;Sthapit, Tuladhar, Marasini, Khoju, & Thapa, 2011). Also there is a shifting trend in susceptibility and resistance of the bacteria towards available antibiotics in the last decade (Adebayo et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Staphylococcus species, Streptococcus pneumonia, and Haemophilus influenza are the most prevalent causative bacteria in adults, and H. influenza, S. pneumonia, and Moraxella catarrhalis infections are most frequently reported in children. 3,4 Based on the course and severity, bacterial conjunctivitis is typically categorized into hyperacute, acute, and chronic forms. Acute conjunctivitis is often defined as conjunctivitis with symptoms lasting 3 to 4 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…Ofloxacin is a second‐generation fluoroquinolone antibiotic, and it is a commonly used first‐line agent in bacterial conjunctivitis. Ofloxacin eye drops are effective against the most common bacteria in bacterial conjunctivitis, such as Gram‐positive Staphylococcus epidermidis , Staphylococcus aureus and Streptococcus pneumoniae and Gram‐negative Haemophilus influenza …”
Section: Introductionmentioning
confidence: 99%